L’innovation Incrementale Comme Vecteur de Developpement de la Croissance Financière des PME Algeriennes: Etude d’un Echantillon de PME Innovantes - Reguig, Abdelmalek; Bentabet, Bouziane (جامعة طاهري محمد، بشار - كلية العلوم الاقتصادية والعلوم التجارية وعلوم التسيير, 2019)
Incremental innovation appears to be one of the major elements of the competitiveness of SMEs, whose in which success and survival depend on their ability to innovate. This work aims to define at which what level the Incremental innovation can impact the financial growth of SMEs in Algeria. Indeed, this paper is based on a study for sambleicludes of a sample of 11 firms (SME own holding a parent) that who integrate incremental innovation in its activity.
Keywords: التخطيط الإستراتيجي -- الإدارة المالية -- إدارة الشركات -- الجزائر